Acute pancreatitis: An initial presentation of systemic lupus erythematosus - Gholamhossein ALISHIRI; Nooshin BAYAT; Hadi KHAJEHPOOR; Mehrdad NOORANIPOUR; Mohammad Ebrahim GHAMARCHEHREH (Turkish Journal of Gastroenterology, 2019)
-